1997
DOI: 10.1136/hrt.77.2.115
|View full text |Cite
|
Sign up to set email alerts
|

Relation between ST segment elevation during dobutamine stress test and myocardial viability after a recent myocardial infarction.

Abstract: The accuracy of ST segment elevation for the prediction of functional improvement was similar to that of low dose dobutamine echocardiography in patients with anterior infarction (80% v 83%) and in patients who underwent revascularisation (78% v 83% respectively). Conclusion-In patients with a recent Q wave myocardial infarction, dobutamineinduced ST segment elevation is a valuable marker of myocardial viability particularly when the test is performed without or with suboptimal echocardiographic imaging.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
10
0
7

Year Published

2000
2000
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 33 publications
3
10
0
7
Order By: Relevance
“…[92][93][94][95][96][97] Le diagnostic de spasme coronaire ne peut être définitivement porté qu'après réalisation d'une coronarographie avec épreuve de provocation par l'ergonovine, l'acétylcholine ou la dobutamine.…”
Section: Geleijnse Et Alunclassified
See 1 more Smart Citation
“…[92][93][94][95][96][97] Le diagnostic de spasme coronaire ne peut être définitivement porté qu'après réalisation d'une coronarographie avec épreuve de provocation par l'ergonovine, l'acétylcholine ou la dobutamine.…”
Section: Geleijnse Et Alunclassified
“…ST-segment elevation in noninfarct leads has also been linked to transmural myocardial ischemia due to severe CAD. [92][93][94][95][96][97] The final diagnosis of coronary spasm can only be confirmed on coronary angiography with ergonovine, acetylcholine, or dobutamine provocation. 85,87 Treatment Sublingual nitroglycerin should be administered first rather than ␤-blocking agents 83,84 because of a small risk of exacerbation of spasm with a ␤-blocker.…”
Section: Pathophysiologymentioning
confidence: 99%
“…Studies of the relationship among stress-induced ST segment elevation, myocardial viability and ischaemia after myocardial infarction have gained increasing interest, particularly in the thrombolytic era, as a large proportion of patients retain viable myocardium which may improve spontaneously or after revascularization [1][2][3][4] . It is important to identify viable myocardium in order to match patients to the most appropriate strategy for improvement of left ventricular function.…”
Section: See Page 814 For the Article To Which This Editorial Refersmentioning
confidence: 99%
“…26 It has been shown that the effect of -adrenergic stimulation on action potential is more prominent in non-infarcted myocardium than in the infarcted territory 27,28 and this generates a difference in the resting and action potentials between the 2 areas, resulting in a current of injury, which would be recorded as ST-segment elevation on ECG. 29 The ST-segment elevation is a valuable marker for myocardial viability, 10 as well as a predictive sign of improvement of myocardial function following acute MI and revascularization. [7][8][9] Positron emission tomography studies have shown that a majority of recently infarcted myocardial regions retain residual metabolic activity in patients showing ST-segment elevation.…”
Section: Mechanism Of Exercise-induced St-segment Elevationmentioning
confidence: 99%
“…It has been interpreted as a sign of myocardial ischemia, 1,2 left ventricular wall motion abnormality (WMA) 3,4 or both, 5,6 and recent studies have suggested that ST-segment elevation during stress reflects myocardial viability. [7][8][9][10][11] Stress echocardiography has been proposed as a useful technique for the assessment of myocardial ischemia, left ventricular dysfunction and myocardial viability, but although exercise and pharmacological stress, such as dobutamine and dipyridamole, are widely used in stress echocardiography, there has not been a comparative study of the significance of the stressinduced ST-segment elevation of exercise, dobutamine and dipyridamole in identical patients. Dobutamine and dipyridamole differ in their mechanism of inducing myocardial ischemia: dobutamine is a -receptor agonist that increases myocardial oxygen consumption, whereas dipyridamole causes vasodilation and induces vertical and horizontal blood steals.…”
mentioning
confidence: 99%